2021
DOI: 10.4014/jmb.2012.12013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ecklonia cava Extract on Neuronal Damage and Apoptosis in PC-12 Cells against Oxidative Stress

Abstract: Marine algae (seaweed) encompass numerous groups of multicellular organisms with various shapes, sizes, and colors, and serve as important sources of natural bioactive substances. The brown alga Ecklonia cava Kjellman, an edible seaweed, contains many bioactives such as phlorotannins and fucoidans. Here, we evaluated the antioxidative, neuroprotective, and anti-apoptotic effects of E. cava extract (ECE), E. cava phlorotannin-rich extract (ECPE), and the phlorotannin dieckol on neuronal PC-12 cells. The antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…By contrast, Lee et al (2019) reported that eckol and dieckol were not toxic up to a concentration of 100 µM. Additionally, Shin et al (2021) reported that dieckol at a concentration of 50 µg mL À1 (approx. 67 µ M) protected PC12 cells against H 2 O 2 (200 µM) (Shin et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…By contrast, Lee et al (2019) reported that eckol and dieckol were not toxic up to a concentration of 100 µM. Additionally, Shin et al (2021) reported that dieckol at a concentration of 50 µg mL À1 (approx. 67 µ M) protected PC12 cells against H 2 O 2 (200 µM) (Shin et al, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…The brain is more vulnerable than other organs to oxidative stress due to the high consumption of oxygen, relatively low levels of endogenous antioxidant capacity and generation of superoxides by the action of various oxidases and nitric oxide synthase (Yavin et al ., 2002). Oxidative stress can impair redox homeostasis and induce mitochondrial dysfunction, leading to damage in neuronal cells (Li et al ., 2020) and H 2 O 2 has previously been used to effectively generate cytosolic oxidative stress (Cai et al ., 2008; Shin et al ., 2021). Our results demonstrated that the fucofuroeckols PFFA and 974‐A were able to prevent H 2 O 2 ‐induced death in PC12 cells, while no protective effects were observed with eckol and dieckol (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations